2008
DOI: 10.1111/j.1530-0277.2008.00817.x
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of the Stimulant Response to Ethanol is Associated with Enhanced Ataxia for a GABAA, but not a GABAB, Receptor Agonist

Abstract: Background: The c-aminobutyric acid (GABA) system is implicated in the neurobiological actions of ethanol, and pharmacological agents that increase the activity of this system have been proposed as potential treatments for alcohol use disorders. As ethanol has its own GABA mimetic properties, it is critical to determine the mechanism by which GABAergic drugs may reduce the response to ethanol (i.e., via an inhibition or an accentuation of the neurobiological effects of ethanol).Methods: In this study, we exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
30
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 87 publications
7
30
0
Order By: Relevance
“…Drugs that block the stimulant effects of ethanol and ethanol-induced sensitization in mice have also shown promise for the treatment of alcohol dependence in humans. For example, baclofen, a γ-aminobutyric acid (GABA)-B receptor agonist, which has shown promise for the treatment of alcohol dependence in some human studies and case reports (see Agabio and Colombo 2014; Leggio et al, 2010 for reviews) was also found to attenuate the stimulant effects of ethanol (Holstein et al, 2009) and ethanol-induced sensitization (Pastor et al, 2010) in mice. Our data suggest that activation of nAChR using a partial agonist may attenuate the locomotor effects of ethanol, which may be important to ethanol addiction.…”
Section: Discussionmentioning
confidence: 99%
“…Drugs that block the stimulant effects of ethanol and ethanol-induced sensitization in mice have also shown promise for the treatment of alcohol dependence in humans. For example, baclofen, a γ-aminobutyric acid (GABA)-B receptor agonist, which has shown promise for the treatment of alcohol dependence in some human studies and case reports (see Agabio and Colombo 2014; Leggio et al, 2010 for reviews) was also found to attenuate the stimulant effects of ethanol (Holstein et al, 2009) and ethanol-induced sensitization (Pastor et al, 2010) in mice. Our data suggest that activation of nAChR using a partial agonist may attenuate the locomotor effects of ethanol, which may be important to ethanol addiction.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, treatment with baclofen has been reported to suppress the following: (1) alcohol drinking in rats exposed to the standard, home cage 2-bottle ‘alcohol versus water' choice regimen (a validated animal model of excessive alcohol consumption in humans) [29,85,86,87,88]; (2) relapse-like drinking in previously abstinent rats [89,90]; (3) alcohol reinforcing and motivational properties in rats, mice and nonhuman primates trained to perform a given amount of ‘work' (usually responding on a lever) to gain access to the alcohol solution [91,92,93,94,95,96,97,98,99]; (4) reinstatement of alcohol-seeking behavior triggered in rats by the noncontingent presentation of a complex of cues previously associated with alcohol availability [100]; (5) alcohol-induced conditioned place preference (CPP; index of alcohol rewarding properties) in mice [101], and (6) alcohol-induced stimulation of locomotor activity in rats and mice (index of alcohol euphorigenic properties) [102,103,104,105]. …”
Section: Baclofen and Sudsmentioning
confidence: 99%
“…Generations of FAST and SLOW mice have revealed that FAST mice have lower ataxic responses to alcohol (Holstein et al 2009; Shen et al 1996), a blunted corticosterone response to alcohol (Boehm et al 2002) and voluntarily consume greater amounts of alcohol (Risinger et al 1994). Moreover, these mice differ in response to several drugs of abuse, behaviorally, neurochemically and neurophysiologically (Beckstead and Phillips 2009; Holstein et al 2005; Meyer et al 2009; Palmer et al 2002; Phillips et al 1992).…”
mentioning
confidence: 99%